Using adaptive architecture to support yoga practices: social considerations for design - Jäger, Nils; Moran, Stuart; Schnädelbach, Holger (2014)
The field of Adaptive Architecture aims to design built environments, which truly adapt to their occupants. ExoBuilding is an in-house prototypical example of Adaptive Architecture, which actuates in response to breathing and heart- rate of its occupants. In this work-in-progress paper, we discuss our aims to apply the technology to the practice of Yoga, in which a core aspect is controlled breathing. We explore the social considerations of deploying this novel technology, and then examine the different possibilities for interaction.